Coach and athlete burnout: The role of coaches` decision-making style - Harris, B. S. (2005)
Recent burnout research has examined coaches and athletes collectively to determine the influence of coach behaviors on coach and athlete burnout. Results revealed a potential incongruity between decision-making behaviors and their influence on coach and athlete burnout. Therefore, the purpose of this study was to examine the relationships between decision-making styles of coaches and burnout among coaches and athletes; gender influence on burnout was also examined. Collegiate swimmers and coaches completed questionnaires assessing burnout and decision-making behaviors. Results revealed a significant relationship between athlete burnout and autocratic coaching behaviors. A significant inverse relationship emerged between athlete burnout and democratic behaviors. ANOVAs revealed no significant interactions between gender and decisionmaking on burnout scores. Significant main effects were found for democratic behaviors on exhaustion and depersonalization subscales; swimmers classified as perceiving fewer democratic behaviors scored higher on these subscales. No significant relationships or gender differences were found with in the coaches.